'Scraggy' dark haloes around bulge-less spiral. Issue 3 (12th April 2019) - Karachentsev, I D; Karachentseva, V E
ABSTRACT: We use a sample of 220 face-on bulge-less galaxies situated in the low-density environment to estimate their total mass via orbital motions of supposed rare satellites. Our inspection reveals 43 dwarf companions having the mean projected separation of 130 kpc and the mean-square velocity difference of 96 km s −1 . For them, we obtain the mean orbital-mass-to- K -band luminosity ratio of 20 ± 3. Seven bulge-less spirals in the Local Volume are also characterized by the low mean ratio, M orb / L K = 22 ± 5. We conclude that bulge-less Sc–Scd–Sd galaxies have poor dark haloes, about two times lower than that of bulgy spiral galaxies of the same stellar mass.